Frugivore Population Biomass, but Not Density, Affect Seed Dispersal Interactions in a Hyper-Diverse Frugivory Network - Genes, Luísa; Losapio, Gianalberto; Donatti, Camila I.; Guimarães, Paulo R.; Dirzo, Rodolfo (Frontiers in Ecology and Evolution, 2022)
Mutualistic interactions are regulated by traits, including body size and population density. In seed dispersal networks, frugivore body size determines the interaction outcome, and species population density determines interaction probability through encounter rates. To date, most studies examining the role of body size and population density on seed dispersal networks have examined animal guilds encompassing a narrow range of body sizes (e.g., birds only). Given non-random, body-size dependent defaunation, understanding the relative role of these traits is important to predict and, ideally, mitigate defaunation effects. We analyzed a hyper-diverse seed dispersal network composed of birds and mammals that cover a wide range of body sizes and population densities in the Brazilian Pantanal. Animal density per se did not significantly explain interaction patterns. Instead, population biomass, which represents the combination of body size and population density, was the most important predictor for most interaction network metrics. Population biomass was strongly correlated with body size, but not with density. Thus, larger frugivore species dispersed more plant species and had more unique pairwise interactions than smaller species. Moreover, species with larger population biomass had the strongest influence (i.e., as indicated by measures of centrality) on other species in the network and were more generalist, interacting with a broader set of species, compared to species with lower population biomass. We posit that the increased abundance of small-sized frugivores resulting from the pervasive defaunation of large vertebrates would not compensate for the loss-of-function of the latter and the inherent disruption of seed dispersal networks.